Professional Sitecore Development - West, John; West, John M (John Wiley & Sons, Incorporated, 2012)
Professional Sitecore Development offers comprehensive information for programmers learning the CMS and experienced Sitecore developers alike. This guidance can help your organization minimize implementation cost and time to web, increasing revenue while decreasing IT costs. With this book, you will learn how to implement solutions with Sitecore, how the Sitecore architecture enhances the ASP.NET development process, how to use Sitecore's extensive Application Programming Interfaces, and how to deploy the website. Professional Sitecore Development provides coverage on a range of topics including: Installing and configuring Sitecore Implementing an information architecture and transforming content into web pages Using the Sitecore security infrastructure, managing errors, and testing automatically Managing Sitecore projects, optimizing performance, and scaling Sitecore solutions Tips, tricks, and best practices for working with the CMS Extending Sitecore and integrating external systems, including coverage of configuration, events, pipelines, and Sitecore's user interface technology If you're looking for a solution for web content management, then Sitecore is your answer and this book will get you started using this valuable software today.